Window-Dressing Objectives of Nepalese Non-Government Organizations: Reasons and Implications - Shrestha, Keshav Prasad (Journal of Advanced Academic Research, 2015)
Non-government organizations in Nepal upped their profile significantly during the deepening armed socio-political conflict in Nepal from 1996 to 2006. New non-government organizations came into being at an increasable speed and the established ones expanded their working profile. As stipulated in Nepalese law, the NGOs are supposed to be purely social organization with not-for-profit motive. This study, however, finds out most of the non-government organizations in Nepal are working to meet vested interest, mainly to satisfy livelihood needs of the non-government organization operators. The window-dressing objectives of Nepalese non-government organization workers have manifold forms ranging from seeking employment to satisfying political interests. The Nepalese government is suggested to tighten up the manipulative operations of non-government organizations by implementing rigid monitoring of non-government organizations operations or open up a policy gateway to register non-government organizations with “earn, survive and serve” objectives. Journal of Advanced Academic Research Vol.1(1) 2014: 36-42